2004
DOI: 10.1148/radiol.2322031069
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography: Feasibility of Substantial Dose Reduction—Comparison of Medium to Very Low Doses in Identical Patients

Abstract: In a feasibility study, the authors compared polyp detection and interobserver variability at computed tomographic (CT) colonography in 15 patients with doses ranging from medium to very low (12.00-0.05 mSv). At levels down to 2% of the medium dose, the mean detection of polyps 5 mm or larger remained at least 74%, while the number of false-positive results decreased and the interobserver agreement remained constant. Initial observations indicate that it is feasible to reduce the radiation dose required for CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 29 publications
1
41
1
Order By: Relevance
“…In view of the inherently high contrast between air and the soft tissue density of body organs, a low-dose protocol was employed for CT, without a loss of diagnostic accuracy. Low-dose protocols for CT have been used in many studies, such as the CT colonography and for detection of occult colonic perforation after colonoscopy [28][29][30] . Low-dose CT is considered to be a standard technique for the evaluation of ME and measurement of the residual gas in the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the inherently high contrast between air and the soft tissue density of body organs, a low-dose protocol was employed for CT, without a loss of diagnostic accuracy. Low-dose protocols for CT have been used in many studies, such as the CT colonography and for detection of occult colonic perforation after colonoscopy [28][29][30] . Low-dose CT is considered to be a standard technique for the evaluation of ME and measurement of the residual gas in the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have demonstrated reduction of CT colonography radiation dose, primarily by decreasing tube current and employing automatic tube current modulation (15,(30)(31)(32)(33). These studies have shown that cutting dose has an effect on the quality of 3D endoluminal renderings, although one study noted that this did not affect perception of polyps 6 mm or larger (30,32).…”
Section: Qualitative 3d Image Analysismentioning
confidence: 99%
“…These studies have shown that cutting dose has an effect on the quality of 3D endoluminal renderings, although one study noted that this did not affect perception of polyps 6 mm or larger (30,32). While prior studies used simulated low-dose data sets, we used true data from two separate acquisitions performed in the same patient on the same scanner at the same time, with the supine examination acting as a control.…”
Section: Qualitative 3d Image Analysismentioning
confidence: 99%
“…The medical literature indicates that the level of ionising radiation received by the patients during the CT examination varies from 5 to 20mSv [36][37][38][39][40][41] and this radiation level may induce cancer in 0.05% of the patients older than 50 years that were subjected to a CT abdominal examination [42]. Cohen [43] indicates in his paper that the risk of inducing cancer in patients is significantly lowered when they are subjected to low-level radiation exposure and an important number of studies were carried out in order to identify the minimal level of radiation dose that can be used in CTC but without a negative impact on the detection of colorectal polyps [41,[44][45][46]. The identification of the optimal scanning parameters (collimation, slice thickness, table speed, reconstruction interval) is a difficult problem and this procedure is applied on synthetic phantoms that are designed to accurately model the human body [47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%